Pharmacokinetics, Safety, and Tolerability of Selonsertib, an Apoptosis Signal-Regulating Kinase 1 (ASK1) Inhibitor, Following First-in-Human Single and Multiple Ascending Doses in Healthy Subjects - Nelson, Cara H.; Etchevers, Kim; Yi, Saili; Breckenridge, David; Hepner, Mischa; Patel, Uptal; Ling, John; Mathias, Anita (Clinical pharmacokinetics, 2020)
Background Selonsertib is a first-in-class inhibitor of apoptosis signal-regulating kinase 1 (ASK1) with therapeutic potential for fibrotic diseases. This phase I study evaluated the safety, tolerability, pharmacokinetics (PK), and food effect of selonsertib in healthy subjects. Methods This was a double-blinded, randomized, placebo-controlled dose-escalation study. Healthy subjects received 1, 3, 10, 30, or 100 mg of selonsertib or placebo as single or multiple doses once daily for 14 days in the fasted state, or 30 mg or placebo single dose in the fed state. Blood and urine (single-dose cohorts only) samples for selonsertib PK were collected and safety was assessed throughout the study. Ex vivo pharmacodynamic (PD) assessment was performed in blood from a separate cohort of healthy donors using an auranofin-stimulated C-X-C motif chemokine ligand 1 (CXCL1) assay. Results Overall, 107 subjects (83 active, 24 placebo) were enrolled and randomized to 11 cohorts. Selonsertib was generally well tolerated; adverse events were generally mild to moderate. Selonsertib was rapidly absorbed with dose-proportional PK of both parent and inactive metabolite GS-607509. There was no food effect on selonsertib PK. Renal excretion was a minor pathway of selonsertib elimination. Selonsertib half maximal effective concentration (EC 50 ) in human whole blood was determined to be 56 ng/mL. Conclusions Selonsertib exhibited a favorable PK profile amenable to once-daily dosing without regard to food. PD data suggest pharmacologically relevant exposures were achieved in the dose range evaluated. Study results support further clinical development of selonsertib.